PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMPUTER MODEL TUTORIAL INERAKTIF UNTUK MATERI POKOK LINGKARAN KELAS VIII SMP/ MTS - Habibah, Ami; Roza, Yenita; ', Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is a developmental research which aims to produce computer-based learning media interactive tutorial model on the subject circle for class VIII SMP/ MTs that is valid and practical. This developmental research used development model based on the teory of Borg and Gall. The stages are: (1) potential and problem; (2) literature collection; (3) product design; (4) product validation; (5) product revision; (6) product tested; (7) product revision; (8) product tested in large group; (9) product revision. In the first stages, the researcher analyzed potentials and problems. After that, the researcher collected the reference materials, then designed the product and put it into a computer. The learning media that had been developed was be evaluated by three validators based on the aspects of learning, display, program and curriculum, and revised according to the advice of the validator. Next, the learning media that had been revised was be tested in two stages: product testing in small groups with the subject of five students of class VIII SMP Juara Pekanbaru and product testing in large groups with the subject of 25 students class VIII SMP Juara Pekanbaru. Based on the results of data analysis and discussion, it can be concluded that the computer-based learning media interactive tutorial model for the subject circle class VIII SMP / MTs assessed valid by experts with an average value of 3.59 and received a very good response from students of class VIIIKeywords: Computer-based Learning Media, Research and Development, Circle